Toward a Sustainable Energy Transition: The Architecture of Islamic Finance in Indonesia's Biogas Sector - Bogy Febriatmoko; M Aulia Rachman; Budiantoro, Risanda A (Universitas Negeri Semarang, 2024)
Indonesia is an agricultural country with abundant potential for bioenergy (biodiesel, bioethanol, biomass, and biogas), with Indonesia's biofuel consumption and production expected to increase by 50 percent. This potential is one of the foundations for reducing carbon emissions by replacing fossil energy with new and renewable energy. Therefore, this study aims to analyze the government's initiative to use biogas through PLTBg. This study uses SWOT analysis through the Berlian Porter model approach with secondary data to prepare a strategic architectural framework. The research results are based on the findings in the development of financing for biogas utilization through PLTBg in the preparation and acceleration (short term), expansion (medium term), and final goal achievement (long term). The financing process uses the build, own, operate, and build-own transfer business model approach by implementing the 5C Principles integrated with ASRI principles. In order to optimize the biogas financing process, an agreement was made between the stakeholders involved to create new and renewable energy efficiency in the biogas sector through PLTBg and create a healthy business climate competition to avoid agency problems. The hope is that when this strategic architecture is used correctly, the acceleration of the transition project in the new renewable energy sector, especially biogas, through PLTBg through a funding scheme or financing for the financial services industry can be realized.